International law as a profession - Practice of law.## Int; Aspremont, Jean; Gazzini, Tarcisio; Gazzini, Tarcisio
"International law is not merely a set of rules or processes, but is a professional activity practised by a diversity of figures, including scholars, judges, counsel, teachers, legal advisers and activists. Individuals may in different contexts play more than one of these roles, and the interactions between them are illuminating of the nature of international law itself. This collection of innovative, multidisciplinary and self-reflective essays reveal a bilateral process whereby, on the one hand, the professionalization of international law informs discourses about the law, and, on the other hand, discourses about the law inform the professionalization of the discipline. Intended to promote a dialogue between practice and scholarship, this book is a must-read for all those engaged in the profession of international law"